Sepiolite-Based Nanogenerator Driven by Water Evaporation - Liwei Zhao; Guoxing Jiang; Xing Zhang; Chunchang Wang (Nanomaterials)
This work introduces a new type of water evaporation-driven nanogenerator (S-WEG) utilizing the natural mineral sepiolite, which capitalizes on its hierarchical nanoporous architecture and intrinsic hydrophilicity to harvest energy from ambient humidity through capillary-driven evaporation. The S-WEG, fabricated via a facile drop-coating drying method, demonstrates remarkable mechanical flexibility and sustained operational reliability. Our results demonstrate that by optimizing evaporation height and width, the S-WEG can generate a short-circuit current of ~0.6 μA and an open-circuit voltage of ~0.9 V. Through series and parallel configurations of multiple S-WEG units, the current and voltage outputs can be effectively amplified to power small-scale electronics.